Archival evidence as a source of memory representation on the history of political repressions - Sydykov Yerlan В.; Zhanbosinova, Albina S.; Sailaubay, Yerlan E.; Maslov, Khalil B. (BULLETIN of the L.N. Gumilyov Eurasian National University. Historical sciences. Philosophy. Religion Series, 2023)
Historical memory as a way of storing and broadcasting past events, being an integral part of human culture, determines many interdisciplinary research approaches. The authors focused on the history of political repressions that left the deepest imprint in the public consciousness of the Kazakh community. Despite the fact that the historiography of the proposed topic has fundamental works, serious scientific publications, new discoveries and interesting results, not all sources of the history of political repressions have become the object of scientific research. The presented author’s research for the first time introduces into scientific circulation fragments of the archival evidence of S. Baibulin’s case, a native of Kazakhstan, who was arrested in the city of Kyiv in 1937, convicted by the Special Council and repressed by the NKVD of the Ukrainian SSR. The case of S. Baibulin was deposited in the archives of the Security Service of Ukraine (SBU). The authors presented a source study analysis of the archival evidence, demonstrated the possibilities and methods of extracting information in order to form the framework / frame of the personal memory of the victim of political repressions. The uniqueness of the scientific content of the article lies in the opportunity to get acquainted with the structure of the archival evidence, as a source of memory representation on the history of political repressions in the focus of the presented ego-documents. Such a representation of memory can be considered as the practice of public commemoration of the victim, whose personal data remained only in a single source - an archival evidence. The authors’ goal was restoring historical justice for the victim of political terror, despite the presence of rehabilitation in accordance with the Law of the Ukrainian SSR "On the rehabilitation of victims of political repression in Ukraine" dated April 17, 1991, S. Baibulin, as a repressed person, does not appear in the camp lists of Belomor-Baltic Forced Labor Camp where he served time, and his data are not included in the lists of those rehabilitated, neither in Ukraine, nor in Kazakhstan.